2006
DOI: 10.1111/j.1365-2249.2006.03188.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins B, L and D in inflammatory bowel disease macrophages and potential therapeutic effects of cathepsin inhibition in vivo

Abstract: SummaryThe cathepsins D (CTSD), B (CTSB) and L (CTSL) are important for the intracellular degradation of proteins. Increased cathepsin expression is associated with inflammatory diseases. We have shown previously an induction of CTSD expression in intestinal macrophages (IMAC) in inflamed mucosa of patients with inflammatory bowel disease (IBD). Here we investigated the regulation of CTSB and CTSL in IMAC during IBD and effects of CTSD and CTSB/CTSL inhibition in vivo. Human IMAC were isolated from normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 30 publications
3
87
0
1
Order By: Relevance
“…Interestingly, expression of both cathepsin S and B has been well documented at inflammatory sites in various disease models including pancreatitis (39), inflammatory bowel disease (40), and atherosclerosis (41). It seems plausible that cathepsin-mediated cleavage of Rip1 kinase could play a role in perpetuating macrophage survival and function within inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, expression of both cathepsin S and B has been well documented at inflammatory sites in various disease models including pancreatitis (39), inflammatory bowel disease (40), and atherosclerosis (41). It seems plausible that cathepsin-mediated cleavage of Rip1 kinase could play a role in perpetuating macrophage survival and function within inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown earlier that expression of tissue-degrading cathepsins B, L, and D may play an important role in the pathophysiology of IBD and that they can provide a new target for IBD therapy. 20 We can speculate that large amounts of Cat-G may be released from neutrophils into tissues but also into the colonic lumen consecutively to epithelial barrier disruption. Interestingly, anti-neutrophil cytoplasmic antibodies targeting Cat-G are found in the sera of more than half of UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, CatL-positive cells (primarily immunocytes) were accumulated in the stromal compartment of the colon during all stages of chronic colitis ( Figure 1G). It has been previously shown that CatL plays an important pathophysiological role in colonic inflammation and that macrophages are the primary cellular source of inducible CatL expression in inflamed colon of UC patients and in acute DSS-induced mouse colitis (62). A different cellular source of heparanase (epithelial) and CatL (stroma/immunocytes) implies that proteolytic processing of heparanase by CatL takes place in the extracellular space.…”
Section: Macrophages Represent Both Cellular Targets For Heparanase Amentioning
confidence: 99%